2016
DOI: 10.1002/admi.201600074
|View full text |Cite
|
Sign up to set email alerts
|

Moldable Superhydrophobic Surfaces

Abstract: Moldable superhydrophobic surfaces are produced by freely covering a solid surface with specifically designed microcapsules. Owing to the presence of Fe‐particles within the former microcapsules, they can be temporarily fixed on different substrates using a permanent magnet. Such systems are prospective candidates for the fabrication of water/oil repellent surfaces, liquid marbles, or microfluidic channels and as templates for microspheres fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Hydrophobic particles can be loosely fixed over flat surfaces to prepare moldable superhydrophobic surfaces . For the case of LM, it was reported that the encapsulating layer of particles can present a structure from a loosely packed monolayer to a multilayer structure.…”
Section: Liquid Marblesmentioning
confidence: 99%
“…Hydrophobic particles can be loosely fixed over flat surfaces to prepare moldable superhydrophobic surfaces . For the case of LM, it was reported that the encapsulating layer of particles can present a structure from a loosely packed monolayer to a multilayer structure.…”
Section: Liquid Marblesmentioning
confidence: 99%
“…In fact, to date a number of approaches have been followed to fabricate compartmentalized hydrogel beads including, double-emulsion strategies, electrospray, and superhydrophobic surfaces. [27][28][29][30][31][32][33] The later comprises the deposition of a polymeric solution on the superhydrophobic surface forming a spherically shaped droplet, while avoiding the use of deleterious solvents. Besides being an organic solvent/oil-free strategy, superhydrophobic surfaces are cost-effective, easily handleable, and enable one to produce polymeric beads of different sizes and with spherical-like morphologies, dependent on the droplet volume and polymer concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Functional micro/nano-objects that are intrinsically rich of hydroxyl groups or can be easily treated to possess hydroxyl groups will be able to serve as the embedding materials for the fabrication of superhydrophobic surfaces while maintaining their own functionalities, such as magnetic ferroferric oxide particles. 44 …”
Section: Discussionmentioning
confidence: 99%